Genetic polymorphism of kappa-casein gene in indigenous Eastern Africa goat populations - Kiplagat, S.K.; Agaba, Morris; Kosgey, I.S.; Okeyo Mwai, Ally; Indetie, D.; Hanotte, Olivier H.; Limo, M.K.H. (2010)
Indigenous goat breeds kept by majority of smallholder rural farmers in Eastern Africa are adapted to the local environment. These goats are critical for nutrition and income of their keepers. Milk production per doe is extremely variable. The variation in milk yield in goats is due to varied management practices and variability in genetic make-up of the animals. The variation in kappa-casein gene and the distribution frequencies of its variants amongst indigenous Eastern Africa goat populations were investigated. A 458 base pairs sequence in exon 4 of 296 goat samples were amplified, sequenced and variation analyzed. Nine point mutations corresponding to base transitions were identified. Three sites were synonymous substitutions while the other six mutations were non-synonymous. All the amino acid substitutions were conservative. Analysis of the association of the mutations yielded nine haplotypes. The occurrence of these haplotypes in ten goat populations indicated that only one haplotype occurred at a rather high frequency. The prevalent κ-casein variant was CSN3*B with frequencies ranging from 0.750 to 0.953. The second most common allele was CSN3*A. Further studies on other casein loci are necessary to establish associations of all the casein mutations and the effects of the haplotypes to milk production traits.